The EM algorithm for general Gaussian model with latent variables - Radavičius, Marijus (Lietuvos matematikos rinkinys, 2010)
The problem of estimating parameters of Gaussian vector when only its (nonlinear) transformation is observed is addressed. The EM algorithm equations to calculate maximum likelihood estimator are derived. In particular, closed-form formulas of the EM algorithm are derived in the case when only the minimum of two endogenous variables satisfying Gaussian regression model is observed.